Real Money Balances as a Variable in the Production Function - Prais, Zmira (The Review of Economics and Statistics, 1975)
a, B, y, and X are stable over the tight and the loose money subsamples is rejected at the 5 %, 10% and 20% significance levels for equations (6), (5), and (4), respectively. (2) The coefficients of m for loose money years is always negative and smaller by about 0.16 to 0.23 than the corresponding coefficient for tight money years. The latter is positive when current I is not included in the equation and becomes negative, even if it is not significantly different from zero, only in equation (5) where current I is added. It is therefore clear that m has a positive influence on output only when tight money prevails. Even in this case, however, its influence is mainly due to its correlation with investment.